Determination of Leisure Levels of Village Patronage UIN Sunan Kalijaga Yogyakarta: Improving Governance Patronage towards Rural Green Village and Environmentally Friendly - Supriatna Supriatna; Thaqibul Fikri Niyartama; Iwan Kuswidi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2016)
This study took place in the village of Patronage UIN Sunan Kalidjaga Yogyakarta that consist of 13 hamlets (Klidon, Banjarsari, Wonosalam, Dongkelsari, Puntuk, Tanjung Sari, Karang Lo, Purworejo, Tanjung, Banturejo, Nglengkong and Surirejo), Sukoharjo Village, District Ngaglik, DIY Sleman regency. Data are collect and analysed in order to obtain results in a level of comfort. The analysis was performed by using a formula based on the comfort level Temperature Humidity Index (THI). The results showed that Hamlet Klidon, Banjarsari, Wonosalam, and Dongkelsari shows Not Comfortable, whereas Hamlet Puntuk, Tanjung Sari, Karang Lo, Purworejo, Tanjung, Banturejo, Nglengkong, Surirejo and Mujen show Strongly Comfortable mainly on the clock 10:00 to 15:00.